Socio-Religious Issues in Alcoholic Consumption among Christian in Selected Orthodox Churches in Surulere Lagos Government, Lagos State - Ogunbiyi, David (RERUM: Journal of Biblical Practice, 2024)
The study employed a combination of qualitative and quantitative approaches to examine Christian knowledge, attitudes, and behaviors on alcohol consumption in Nigeria, with a focus on members of selected Orthodox churches in Surulere Local Government of Lagos State. The study utilized a mixed-methods approach, incorporating both qualitative and quantitative data, utilizing structured interviews, focus group discussions, and surveys to gather insights from church members. Participants were drawn from Anglican, Methodist, Baptist, and Catholic churches. A total of 188 Orthodox Christians were interviewed, and 180 respondents completed the study questionnaire. Results showed that respondents between the ages of 22-67 years were interviewed. The mean age was 36.07% years, Sd +/- 7 years, 60% were married and 20% were single. The majority (60.5%) were male, 65% adults. It also shows that 37.8% have spent between 5-6 years in their local churches, and 58% have served in different capacities. The biblical position, health, and social knowledge about alcohol consumption are very high among the respondents. About 67.2% supported Christian can consume alcohol, and 67.8% believed it can affect their spiritual life. However, 39.4% reacted as very inappropriate to serve alcohol at church functions. The majority (69%) consume due to stress, in the party, among friends but believe it has to be in moderation. It was concluded that though the Bible has not specifically ruled against alcohol consumption but to be with all moderation.